A Complex Post-Transplant Puzzle: Successful Intervention in Chronic Allograft Dysfunction with Portal Biliopathy and Portal Vein Thrombosis - B, Adhiraj.; S, Shanmugachandru.; T, Immanuvel.; Angel.S, Jacintha Abisha; Karthickeyan, K.; Sundaram, P. Shanmuga; Sri, M.K. Sundar (Journal of Neonatal Surgery, 2025)
We report a case of a 38-year-old female who presented with gastrointestinal symptoms eight years after a deceased donor liver transplantation performed for autoimmune hepatitis. She was found to have chronic allograft dysfunction complicated by portal biliopathy, portal vein thrombosis, ascites, and anemia. Her management involved percutaneous transhepatic biliary drainage (PTBD), terlipressin infusion, blood product transfusions, and optimization of immunosuppressive therapy. This case highlights the complex nature of long-term complications following liver transplantation and emphasizes the importance of multidisciplinary management in such cases.